2023
DOI: 10.1051/parasite/2023005
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose-fractionation in adult Aedes aegypti mosquitoes

Abstract: Balancing process efficiency and adult sterile male biological quality is one of the challenges in the success of the sterile insect technique (SIT) against insect pest populations. For the SIT against mosquitoes, many stress factors need to be taken into consideration when producing sterile males that require high biological quality to remain competitive once released in the field. Pressures of mass rearing, sex sorting, irradiation treatments, packing, transport and release including handling procedures for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…These findings establish an optimal window for using irradiation to target the female germline for sterilization. In the SIT approach, higher irradiation doses, ranging from 35 to 70 Gy, are applied in order to achieve a 99% male sterility [37,[48][49][50]. It is worthwhile to note that most of these studies use a Gamma radiation source.…”
Section: Discussionmentioning
confidence: 99%
“…These findings establish an optimal window for using irradiation to target the female germline for sterilization. In the SIT approach, higher irradiation doses, ranging from 35 to 70 Gy, are applied in order to achieve a 99% male sterility [37,[48][49][50]. It is worthwhile to note that most of these studies use a Gamma radiation source.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies based on dose fractionation showed the same trend with improved male performance, i.e., induced sterility, longevity, or mating competitiveness in insect pests of crops, livestock, and vectors of human diseases [52]. Fractionation of the radiation doses applied to the Indian meal moth, Plodia interpunctella showed a significant improvement of male longevity, mating competitiveness, and sterility [14], and similarly, a significant improvement was obtained in male Aedes aegypti's survival and mating competitiveness [67]. Dose fractionation applied to Glossina morsitans increased their residual fertility as compared with a similar but continuous single dose [21].…”
Section: Introductionmentioning
confidence: 99%
“…The SIT can only be successful when the colony-reared and released sterile males are as competitive as their wild counterparts to mate with wild females [61]. To produce high-quality sterile males for use in SIT programs, factors and processes such as the rearing, sterilization, transport, handling and release must be considered and properly managed as they are the critical factors that can affect the quality of the sterile males [67,69].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in some facilities, the optimum dose for Aedes albopictus is reported to be between 35 and 40 Gy whereas it is 50 Gy for Aedes aegypti 20 , 24 , 29 , 30 . Other facilities require 55 Gy and 70 Gy for the two species respectively 21 , 31 , 32 . Dose–response is also affected significantly by atmospheric conditions during irradiation, and particularly oxygen levels have been shown to have significant impact on irradiation outcome 25 , 33 .…”
Section: Introductionmentioning
confidence: 99%